Empowerment of Anti-Money Political Villages to Create Elections with Integrity - Sri Wahyuni; Agus Riwanto; Achmad Achmad; Sunny Ummul Firdaus (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
Pilkada is one form of democracy in the regions that need to be ensured that its implementation is in accordance with procedures so as not to lose the meaning of democracy itself. Bawaslu has an essential role in realizing elections with integrity without the practice of money politics. One of the tasks of Bawaslu is to prevent the practice of money politics. One of the crucial components in the implementation of regional head elections (Pilkada) is the village and its citizens. The village, which is the closest component to the community in the election, becomes a place for the practice of money politics. The integrity of the Pilkada can be destroyed because of the practice of money politics that occurs in the village. A strategy to prevent money politics is needed in the village by building an anti-money politics village in order to strengthen local democracy.